Code Switching In The Use Of Java Language In Clearing Buying And Buying Transactions - Siti Rifka; Kholifah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
This research aims to describe: (1) the use of language in clothing buying and selling transactions (2) the factors causing code switching. (3) code in Javanese. The data for this research are the speech of sellers and buyers which contain code switching. The data sources in this research are sellers and buyers who carry out clothing buying and selling transactions. The data collection method used was the reading and note-taking method. The technique used was note-taking technique. This research data was analyzed using qualitative descriptive methods The results of this research show that in clothing buying and selling transactions using Javanese, both sellers and buyers often use speech that contains code switching. Forms of code switching include language code switching, namely code switching from Indonesian to Javanese or vice versa. Factors causing code switching are the speaker, the interlocutor, the presence of a third party, and generating a sense of humor.